A comparison of the effect of chlorhexidine,tap water and normal saline on healing wounds (2006)
Many researchers have advocated in recent times that antiseptic use in healing wounds should be discouraged. Antiseptics have been found to retard healing of wounds. Innocuous solutions like normal saline and tap water are being considered as better alternatives to antiseptics. Chlorhexidine, a commonly used antiseptic, is known to be less toxic on granulation cells. We decided to compare the effect of chlorhexidine, normal saline and tap water on healing wounds. Three groups of wistar rats had 2 by 2cm full thickness wounds made on their right dorsolateral flanks. The wounds were dressed with either chlorhexidine, normal saline or tap water. Wounds were examined at three-day intervals and measurements of area covered were taken on the first day of study and the ninth day. Wound contraction on the ninth day and number of days for healing to take place in the different groups was taken and statistical analysis using student t-test was done to compare the values. Gross morphology of the wounds was also observed. The result showed an inhibitory effect of chlorhexidine on healing wounds. The wound contraction in the antiseptic group was less than the tap water and saline group on day nine. The average number of days for wound healing to be completed in the antiseptic group was more than the other two. These results were statistically significant when compared with the other two groups. There was no statistical difference in the wound contraction values and rate of healing of the saline and tap water dressed wounds. Grossly, all the wounds dressed with antiseptic also had greenish exudates on their surface by day nine with pale looking granulation tissue, and there was greater mortality in this group.